(untitled) (FULafia Journal of Science and Technology, 2018)
This research work evaluated the potentials of earthworms in the treatment of organically polluted water. Physiochemical parameters tested based on APHA standards to evaluate the qualities of water were Biolgical Oxygen Demand(BOD), Chemical Oxygen Demand(COD), Total Soluble Solids(TSS), Total Dissolved Solid (TDS), Electrical conductivity, pH, and temperature. The experiment was carried out in three batches in a vermi-filter where mass and time was varied to evaluate the removal efficiencies of organic matter from waste water samples using the physiochemical parameters. The results of the experiment showed that the removal percentages of BOD, COD, TSS, TDS was between 65.5 - 80%, 68.2-85.8%, 59.1-92.7% and 60.6-91.5% respectively depending on the hydraulic retention time of the waste water in the vermifilter and masses of the earthworm in each vermin-filter. Earthworm successfully treated organically polluted water.